Evaluation of the Implementation of Distance Education Social Studies Curriculum in Ghana - Augustus Daniel Arko; Ebenezer Kporyi (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
This study investigated the implementation of distance education Social Studies curriculum in Ghana. A concurrent embedded mixed-method design was used for the study. Four research questions were formulated to guide the study. The population for the study consisted of all 168 Social Studies tutors of the College of Distance Education, University of Cape Coast, and data was gathered from questionnaire interviews and observations. The mean and standard deviation were used to analyse research questions one, three, and four, while thematic analysis was performed for research question two. The results revealed that the study centres of the college had inadequate physical facilities and instructional materials. Also, the primary instructional methods used by tutors at the college were discussion, expository, inquiry, discovery, role-play, and comparative learning methods but there was a lack of motivational packages for tutors. Furthermore, Social Studies tutors were found to have a high level of self-efficacy for students’ engagement and were efficient in helping students to think critically about social issues. Recommendations were made for the improvement of facilities as well as instructional materials.